The Swedish Media Debate on GMO Between 1994 and 2018: What Attention was Given to Farmers' Perspectives?. Issue 1 (2nd January 2022) - Fischer, Klara; Hess, Sebastian
ABSTRACT: This paper presents a longitudinal study of the debate on GMO in the Swedish media, comparing coverage of the topic in the general press and agricultural press. We studied 1399 articles about GMO in food and agriculture published between 1994 and 2018 in Sweden's daily and evening newspapers and agricultural publications. A combination of content analysis and statistical simulation techniques was used to identify structural breaks in the dataset and contribute understanding about how the debate shifted over time. Particular attention was paid to issues of importance to farmers in the Swedish media discourse. Our findings indicate that the debate was most intense in the mid-1990s, after which the frequency of reporting on GMOs declined overall and the debate steadily became less negative. Farmers' perspectives were given more attention than expected in the general media but, surprisingly, smallholder farming and food security in the Global South, which has been central to global and elite debates on GMO, did not appear to substantially affect media discourses in Sweden.